2004
DOI: 10.1037/0022-0663.96.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Cognitive Functioning in Bilingual and Nonbilingual Children at or Not at Risk for Reading Disabilities.

Abstract: The authors determined whether the cognitive processes that underlie second-language acquisition difficulties are the same as those that underlie reading difficulties. First-grade (N ϭ 101) bilingual and nonbilingual children were administered a battery of measures in Spanish and English. English word identification and vocabulary were predicted by a language-general working-memory (WM) factor, whereas English pseudoword reading was predicted by Spanish pseudoword reading and WM. The results also showed that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 49 publications
12
104
2
Order By: Relevance
“…This call for research is equally relevant for school-age populations in all languages, given the field's limited understanding of this multicomponential construct beyond the fact that it is predictive of literacy (Vukovic & Siegel, 2006). Additional research is also needed to investigate the developmental relations of Spanish RAN with other Spanish phonological processing abilities, especially given that Swanson and colleagues found only limited evidence for the distinguishableness of RAN from phonological short-term memory in native Spanish-speaking and bilingual first grade children in the United States (Swanson, Saez, Gerber, & Leafsteadt, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This call for research is equally relevant for school-age populations in all languages, given the field's limited understanding of this multicomponential construct beyond the fact that it is predictive of literacy (Vukovic & Siegel, 2006). Additional research is also needed to investigate the developmental relations of Spanish RAN with other Spanish phonological processing abilities, especially given that Swanson and colleagues found only limited evidence for the distinguishableness of RAN from phonological short-term memory in native Spanish-speaking and bilingual first grade children in the United States (Swanson, Saez, Gerber, & Leafsteadt, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The first is that although learning a second language places demands on WM, the majority of studies implicate phonological STM (e.g., see Baddeley, Gathercole, & Papagno, 1998;Gathercole, Willis, Emslie, & Baddeley, 1992;Linck, Osthus, Koeth, & Bunting, 2013) and not the executive system. For example, children's new word learning ability in their second language and L2 vocabulary is predicted by phonological memory in their first language (e.g., Engle de Abreau & Gathercole, 2012;Lipka & Siegel, 2007;Stanovich & Siegel, 1994;Swanson, Sáez, Gerber, & Leafstedt, 2004;Thorn & Gathercole, 1999;Thorn, Gathercole, & Frankish, 2002). Thus, children with relatively poor phonological memory are less successful in L2 acquisition and in learning the sound structure of new words (e.g., see Genesee & Geva, 2006, for a review).…”
Section: Differentiating Storage From Executive Processingmentioning
confidence: 97%
“…Branum-Martin et al (2006) examined Spanish-English bilingual children's skills at both student and classroom levels and found a high degree of overlap between Spanish and English PA constructs, although statistically, the two constructs were distinct. However, despite variation between the languages in terms of phonemes, phonotactic constraints, syllable structure, and word length, investigators have found consistent evidence of skill transfer from Spanish to English (e.g., August, Calderon, & Carlo, 2002;Branum-Martin et al, 2006;Cisero & Royer, 1995;Dickinson, McCabe, Clark-Chiarelli, & Wolf, 2004;Durgunoglu, Nagy, & Hancin-Bhatt, 1993;Swanson, Saez, Gerber, & Leafstedt, 2004). This research has important educational implications for instructing ELL students.…”
Section: Pa Development In Ellsmentioning
confidence: 99%